Disintegration Testing of Biodegradable Poly(L-lactide) / Thermoplastic Polyurethane Melt Blended Films - Kanyarat Suthapakti (Science Faculty of Chiang Mai University, 2019)
Poly(L-lactide) (PLL) has been blended with a polycaprolactone-based thermoplastic polyurethane (TPU) elastomer as a toughening agent for potential use as a biodegradable film packaging material. The effects of adding a synthesized poly(L-lactide-co-caprolactone) (PLLCL) copolymer as a compatibilizer was also studied. Both 2-component (PLL/TPU) and 3-component (PLL/TPU/PLLCL) blends were prepared by melt mixing, hot-pressed into thin films and their compostability characterized in a standard ISO disintegration test under controlled laboratory-scale conditions. The results showed that both the 2- and 3-component blended film samples (25 ด 25 mm) disintegrated completely (100%) to fragments less than 2 mm in size within 30 days. These results were similar to those for PLL alone which indicated that neither the TPU nor the PLLCL had retarding effects on the PLL’s biodegradability. It is concluded that both the PLL/TPU and PLL/TPU/PLLCL blends meet the criteria for disintegration and compostability under simulated composting conditions.